“Hak Untuk Dilupakkan” Policy Model: Between Right to Be Forgotten and Right to Erasure - Rifqi Noval, Sayid Mohammad (Asian Crime and Society Review, 2019)
After the enactment of Law No. 19 of 2016 on the Amendment to Law No. 11 of 2008 on Electronic Information and Transactions (EIT Law) in Indonesia, an assessment of new right was born through the Article 26 of the Act, known as the Indonesian version of the “Right to be Forgotten (RTBF).” As a country that has just regulated this right, a similar concept is applied in the European Union Countries. This paper examines the comparison of the “Hak untuk Dilupakkan” model contained in the EIT Law in Indonesia, with the provisions of RTBF based on Directive 95/46/EC which was considered by some legal scholars as the beginning of this concept, begins to grow and is widely known, and right to erasure (RTE) contained in the General Data Protection Regulation (GDPR) which is considered to be a new RTBF related policy that came into force in May 2018. The Hak untuk Dilupakkan model is not entirely similar to the concepts of RTBF and RTE. However, the differences that exist between Hak untuk Dilupakkan, RTBF and RTE still adhere to the main concept to give the right to someone to submit an effort to erase the related data about him / her who is widely available on the internet.